Persepsi Masyarakat Terhadap Bank Syariah Indonesia (Public Perception of Bank Syariah Indonesia) - M. Soleh Mauludin; Agestina Pinatih (Al-Muraqabah: Journal of Management and Sharia Business, 2021)
The research aims to see the extent of public perception of Indonesian Islamic banks. The object of this research is the customers of Islamic banks in the city of Kediri. By using a qualitative and descriptive approach, as well as perception theory, this study concludes that the function and existence of Islamic banking is not only a place for saving or Islamic transactions but also a place to increase worship values. This public perception can be seen in people's understanding of the relationship between Islam and Islamic banking. The public can understand the involvement of Islamic teachings in every activity in Islamic banking. Public perception of the decision to choose to bank is a process of interpreting the object of perception, namely Islamic banking, whether concrete or not, and this is influenced by knowledge in the form of information, experience, motivation, and desires according to their needs.